Impact of Age and Sex on Outcomes and Hospital Cost of Acute Asthma in the United States, 2011-2012. - Joe G Zein; Belinda L Udeh; W Gerald Teague; Siran M Koroukian; Nicholas K Schlitz; Eugene R Bleecker; William B Busse; William J Calhoun; Mario Castro; Suzy A Comhair; Anne M Fitzpatrick; Elliot Israel; et al. (PLoS ONE, 2016)
Background Worldwide, asthma is a leading cause of morbidity, mortality and economic burden, with significant gender and racial disparities. However, little attention has been given to the independent role of age on lifetime asthma severity and hospitalization. We aimed to assess the effect of age, gender, race and ethnicity on indicators of asthma severity including asthma related hospitalization, mortality, hospital cost, and the rate of respiratory failure. Methods We analyzed the 2011 and 2012 Healthcare Cost and Utilization Project- National Inpatient Sample (NIS). We validated and extended those results using the National Heart, Lung, and Blood Institute-Severe Asthma Research Program (SARP; 2002-2011) database. Severe asthma was prospectively defined using the stringent American Thoracic Society (ATS) definition. Results Hospitalization for asthma was reported in 372,685 encounters in 2012 and 368,528 in 2011. The yearly aggregate cost exceeded $2 billion. There were distinct bimodal distributions for hospitalization age, with an initial peak at 5 years and a second at 50 years. Likewise, this bimodal age distribution of patients with severe asthma was identified using SARP. Males comprised the majority of individuals in the first peak, but women in the second. Aggregate hospital cost mirrored the bimodal peak distribution. The probability of respiratory failure increased with age until the age of 60, after which it continued to increase in men, but not in women. Conclusions Severe asthma is primarily a disease of young boys and middle age women. Greater understanding of the biology of lung aging and influence of sex hormones will allow us to plan for targeted interventions during these times in order to reduce the personal and societal burdens of asthma.